Expression of Nerve Growth Factor (NGF), TrkA, and p75NTR in Developing Human Fetal Teeth - Mitsiadis, Thimios A.; Pagella, Pierfrancesco (Frontiers in Physiology, 2016)
Nerve growth factor (NGF) is important for the development and the differentiation of neuronal and non-neuronal cells. NGF binds to specific low- and high-affinity cell surface receptors, respectively, p75NTR and TrkA. In the present study, we examined by immunohistochemistry the expression patterns of the NGF, p75NTR, and TrkA proteins during human fetal tooth development, in order to better understand the mode of NGF signaling action in dental tissues. The results obtained show that these molecules are expressed in a wide range of dental cells of both epithelial and mesenchymal origin during early stages of odontogenesis, as well as in nerve fibers that surround the developing tooth germs. At more advanced developmental stages, NGF and TrkA are localized in differentiated cells with secretory capacities such as preameloblasts/ameloblasts secreting enamel matrix and odontoblasts secreting dentine matrix. In contrast, p75NTR expression is absent from these secretory cells and restricted in proliferating cells of the dental epithelium. The temporospatial distribution of NGF and p75NTR in fetal human teeth is similar, but not identical, with that observed previously in the developing rodent teeth, thus indicating that the genetic information is well-conserved during evolution. The expression patterns of NGF, p75NTR, and TrkA during odontogenesis suggest regulatory roles for NGF signaling in proliferation and differentiation of epithelial and mesenchymal cells, as well as in attraction and sprouting of nerve fibers within dental tissues.